2013
DOI: 10.1111/clr.12280
|View full text |Cite
|
Sign up to set email alerts
|

Dimensional changes in soft tissues around dental implants following free gingival grafting: an experimental study in dogs

Abstract: The increase in the alveolar mucosal thickness by means of a gingival graft affected the peri-implant marginal bone resorption and soft tissue recession around implants. This resulted in outcomes that were similar to those at implants surrounded by masticatory mucosa, indicating that gingival grafting in the absence of keratinized mucosa around implants may reduce the resorption of the marginal crest and soft tissue recession.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
28
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 29 publications
(35 citation statements)
references
References 36 publications
7
28
0
Order By: Relevance
“…41 Moreover, increasing the band of keratinized mucosa with free gingival grafts was found to reduce soft tissue recession and resorption of crestal buccal bone for the short term. 42 More research in the arena is required to understand the etiology of implant recessions and their correction.…”
Section: Hard Tissuementioning
confidence: 99%
“…41 Moreover, increasing the band of keratinized mucosa with free gingival grafts was found to reduce soft tissue recession and resorption of crestal buccal bone for the short term. 42 More research in the arena is required to understand the etiology of implant recessions and their correction.…”
Section: Hard Tissuementioning
confidence: 99%
“…16 It was further shown that the use of a connective graft placed between the alveolar mucosa and the implant shoulder at installation may counteract this outcome. 17 The resorption of the buccal bony plate was slightly higher at the Straumann compared with the Medentis implants. The difference was not statistically significant.…”
Section: Discussionmentioning
confidence: 92%
“…When alveolar nonkeratinized mucosa is present around the implant at installation, a higher bone resorption is expected compared with sites with keratinized mucosa . It was further shown that the use of a connective graft placed between the alveolar mucosa and the implant shoulder at installation may counteract this outcome …”
Section: Discussionmentioning
confidence: 99%
“…The 2017 World Workshop on the Classification of Periodontal and Peri‐Implant Diseases and Conditions reported that MT may influence peri‐implant bone stability even in the absence of soft tissue inflammation . Prospective human studies and experiments in dog models indicate that peri‐implant bone stability may improve when thin native peri‐implant mucosa is thickened using soft tissue grafting procedures …”
Section: Introductionmentioning
confidence: 99%
“…4 Prospective human studies and experiments in dog models indicate that periimplant bone stability may improve when thin native peri-implant mucosa is thickened using soft tissue grafting procedures. 16,[20][21][22][23] Implant sites lacking adequate KMW and MT may be augmented using subepithelial connective tissue graft (SCTG), epithelialized palatal graft (EPG), acellular dermal matrix (ADM), or other biomaterials. 16,[20][21][22][23] The graft or biomaterial is, in most such techniques, placed between the periosteum and bone or on a bed of supraperiosteal connective tissue, with or without advancement of a mucoperiosteal flap.…”
Section: Introductionmentioning
confidence: 99%